Describing the initial results of a pragmatic, cluster randomized clinical trial to examine the impact of a multifaceted digital intervention for the prevention of type 2 diabetes mellitus in the primary care setting: intervention design, recruitment strategy and participants’ baseline characteristics of the PREDIABETEXT trial - Sofía Mira-Martínez; Sofía Mira-Martínez; Sofía Mira-Martínez; Rocío Zamanillo-Campos; Rocío Zamanillo-Campos; Rocío Zamanillo-Campos; Narges Malih; Narges Malih; Narges Malih; Maria Antonia Fiol-deRoque; Maria Antonia Fiol-deRoque; Maria Antonia Fiol-deRoque; et al. (Frontiers in Endocrinology)
Introductioni) to describe PREDIABETEXT, a novel digital intervention for the prevention of type 2 diabetes; ii) to examine the performance of a strategy for virtual recruitment of participants in a trial to assess its impact, and; iii) to determine the baseline characteristics of the enrolled participants.MethodsWe developed PREDIABETEXT in a multistage process involving systematic literature reviews and qualitative research with end users (primary care patients and professionals). We combined multiple virtual strategies (SMS, phone calls, promotional videos) to recruit healthcare professionals and their patients. We collected baseline data from patients (sociodemographic, behavioral and clinical) and healthcare professionals (sociodemographic and professional experience).ResultsThe intervention consisted in delivering personalized short text messages supporting lifestyle behavior changes to people at risk of type 2 diabetes; and online training to their primary healthcare professionals. We recruited 58/133 (43.6%) professionals (30 doctors; 28 nurses) from 16 centers. Most professionals (83%) were women [mean (SD) age 49.69 (10.15)]. We recruited 365/976 (37.4%) patients (54.5% women, 59.82 (9.77) years old. Around half (55.3%) presented obesity (BMI ≥25), 65% hypertension, 43.3% hypercholesterolemia, and 14.8% hypertriglyceridemia.ConclusionsThe PREDIABETEX trial successfully recruited a representative sample of patients at risk of type 2 diabetes and their healthcare providers.